Mating system of a population of Myracrodruon urundeuva F.F. & M.F. Allemão using the fAFLP molecular marker - Freitas, Miguel L.M. [UNESP]; Sebbenn, Alexandre M.; Moraes, Mario L.T. [UNESP]; Lemos, Eliana G.M. [UNESP] (Sociedade Brasileira de Genética, 2004)
The mating system and genetic diversity were studied in a natural population of Myracrodruon urundeuva originating from 30 open-pollinated trees at the Paulo de Faria Ecological Station, SP, Brazil. The progenies were planted on the Teaching and Research Farm of the Ilha Solteira Engineering School, UNESP. Using the fAFLP molecular marker, eleven loci were selected to study the mating system. The mating system was analyzed using the multilocus mixed-mating model. The estimates of genetic divergence between pollen and ovule allele frequencies were significant for eight loci, suggesting nonrandom outcrossing. The estimates of the multilocus outcrossing rate revealed that M. urundeuva possesses a mating system with a predominance of outcrossing events (theta = 0.940 ± 0.086). The estimates of coancestry among plants within progenies (theta = 0.185) was higher than that expected for half-sib progenies (0.125) and the indirect estimate of the correlation of outcrossed paternity within progeny arrays (r p) was 0.403, suggesting that progenies have a high proportion of full-sibs. Result analysis suggests the need for the application of biometric models that take into account deviations from random outcrossing in the estimations of genetic parameters for quantitative traits and the need for retaining large sample sizes in order to preserve genetic variability.
Keywords: Myracrodruon urundeuva; mating system; fAFLP; Molecular marker; correlation of paternity